Studi Parametrik pada Flapping-Wing MAV dengan Bentuk Sayap Belalang, Kupu-kupu dan Kumbang - Yudhono, Reo; Erissonia, Arfie Armelia; Ardianto, Haris (Sekolah Tinggi Teknologi Adisutjipto, 2017)
Nature has been a great inspiration for engineering design. Flying insect, in specific, has been studied and being an inspiration in the development of flapping-wing micro aerial vehicle (FW-MAV). Each species of flying insect has its own wing kinematics, but most all of them generate the aerodynamic force with the same of three mechanism: delayed stall, rotational circulation and wake capture[1]. In this research, we conduct a parametric study on the FW-MAV with different wing shapes. There are two designs of the FW-MAV in this study, which have flapping angle of 80 and 120 deg. The three different shapes of wings are mimics from: desert locust, Monarch butterfly and rhinoceros beetle. The wings then attached to the FW-MAV and operated with voltage input of 1.5V. The force generated by the FW-MAV and the electrical current measured in a swing test, while recorded in 240 fps using action camera. From the test, we get the flapping frequency, generated horizontal force and power consumption. From this research we have several data that can be used for the further development of the FW-MAV.